Opisthorchis felineus Infection and Harmful Metals Bio-Concentration: A Pilot Study in Hamster Model; Advanced Materials Research; Vol. 1085 : Prospects of Fundamental Sciences Development (PFSD-2014) - Lezhava S. P. Sofia P.; Pershina A. G. Aleksandra Gennadievna; Kokova D. A. Darya A.; Perina E. A. Ekaterina A.; Kaminskii I. P. Ilya P.; Сазонов А. Э. Алексей Эдуардович; Ogorodova L. M. Ludmila M. (Material Science in Biology and Medicine, 2015)
Title screen